Glaciotectonic Structures in Central Sweden and their Significance for Glacial Theory - Aber, James; Lundqvist, Jan (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1988)
ABSTRACTVarious glaciotectonic structures and landforms created by ice pushing are common in drift and interstadial sediments in a narrow belt of central Sweden. Described examples from the Lake Storsjôn vicinity demonstrate that glaciotectonic deformation took place while the area was deeply covered by the last Fennoscandian Ice Sheet. Deformation was controlled by pressure gradients related to position of the ice divide and ice movement away from the divide. As the position of the divide shifted during the last glaciation, so did the orientation of glaciotectonic structures. The regional distribution of glaciotectonic features in Fennoscandia falls into three zones: (1) inner zone of widespread, small- to moderate-sized features in older drift, (2) intermediate zone of small, isolated features in drift of the last glaciation, and (3) outer zone with all manner of large and small features in drift and soft bedrock. These zones are the cumulative results of multiple glaciations and reflect the overall distribution of deformable sediment and bedrock within the continental substratum.